Between speaking out in public and being person-centred: collaboratively designing an inclusive archive of learning disability history. Issue 8 (14th September 2018) - Brownlee-Chapman, Chloe; Chapman, Rohhss; Eardley, Clarence; Forster, Sara; Green, Victoria; Graham, Helen; Harkness, Elizabeth; Headon, Kassie; Humphreys, Pam; Ingham, Nigel; Ledger, Sue; May, Val; et al.
Abstract: The Living Archive of Learning Disability History is being developed by an inclusive team of researchers both with and without learning disabilities. We argue the archive is important in making publicly visible the lives of people with learning disabilities. Yet – drawing on thinking that came out of our collaborative workshops – we also identify alternative imperatives, that you might want to have control over how you share your personal memories and stories, with whom, when you share them and for how long. We show how we are responding to these different ideas in the design of the Living Archive in order to create pathways between two traditions that have emerged through self-advocacy: 'speaking out in public' and 'being person-centred'. We outline our research on consent processes to ensure that our archive builds capacity for as many people as possible to consent while also offering a legally compliant 'Best Interests' process in line with the requirements of the Mental Capacity Act, England and Wales (2005). We argue that deploying and actively navigating between the different political logics of 'speaking out in public' and 'being person-centred' offers a way forward for ongoing debates concerning community engagement in archives, museums and heritage.